Multispecific Antibody Development Platform Based on Human Heavy Chain Antibodies - Clarke, Starlynn C.; Ma, Biao; Trinklein, Nathan D.; Schellenberger, Ute; Osborn, Michael J.; Ouisse, Laure-Hélène; Boudreau, Andrew; Davison, Laura M.; Harris, Katherine E.; Ugamraj, Harshad S.; Balasubramani, Aarti; Dang, Kevin H.; et al. (Frontiers in Immunology, 2019)
Heavy chain-only antibodies (HCAbs) do not associate with light chains and their VH regions are functional as single domains, forming the smallest active antibody fragment. These VH regions are ideal building blocks for a variety of antibody-based biologics because they tolerate fusion to other molecules and may also be attached in series to construct multispecific antibodies without the need for protein engineering to ensure proper heavy and light chain pairing. Production of human HCAbs has been impeded by the fact that natural human VH regions require light chain association and display poor biophysical characteristics when expressed in the absence of light chains. Here, we present an innovative platform for the rapid development of diverse sets of human HCAbs that have been selected in vivo. Our unique approach combines antibody repertoire analysis with immunization of transgenic rats, called UniRats, that produce chimeric HCAbs with fully human VH domains in response to an antigen challenge. UniRats express HCAbs from large transgenic loci representing the entire productive human heavy chain V(D)J repertoire, mount robust immune responses to a wide array of antigens, exhibit diverse V gene usage and generate large panels of stable, high affinity, antigen-specific molecules.